Fabrication of a thermally conductive silicone composite by incorporating surface-modified boron nitride. Issue 13 (July 2019) - Kuo, Chung-Feng Jeffrey; Dewangga, Garuda Raka Satria; Chen, Jiong-Bo
Digitization in the textile industry provides an effective manufacturing process; however, the integration of automation with computerization requires an excellent computer support system with a long lifespan. The lifespan of a computer is dependent on the heat generated from the system. The use of heatsinks combined with elastomeric thermal pads is a solution for heat dissipation. Silicone rubber composites exhibit excellent thermal conductivity with the incorporation of boron nitride (BN) as a filler. In this study, tetraethoxy orthosilicate (TEOS), a silane coupling agent, was doped onto to the surface of hydroxyl-functionalized BN using a simple sol–gel process for surface modification. The addition of BN filler up to 45 wt% enhanced the thermal conductivity of the composites and the surface modification of BN had an appreciable effect on the thermal conductivity, with a 16.52% improvement. The addition of TEOS improved the filler dispersion in the composite system and reduced the interfacial mismatch between the BN and silicone rubber. The tensile strength and hardness increased with the addition of the BN filler, but elongation at the break decreased at high filler loadings. Surface modification with 7 wt% TEOS improved the mechanical properties of the composite.